Islam in the digital age : e-jihad, online fatwas and cyber Islamic environments - Bunt, Gary R. (Critical studies on Islam., 2003)
'A fascinating exploration of religion and technology as manifested in cyberspace.' Professor Carl Ernst, University of North Carolina.